IMPROVING SPEAKING SKILLS AND CURIOSITY CHARACTERS THROUGH THE TALKING STICK LEARNING MODEL - Kostansa Yopo; Agus Kichi Hermansyah2; Dewi Puji Rahayu (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to improve speaking skills and curiosity characters through the Talking Stick learning model. This research was classroom action research with Kurt Lewin's model. This research consisted of four stages in each cycle; planning, implementing, observing, and reflecting. This research was conducted at SD YPPK St. Agustinus Erambu. The research subjects were 12 students at grade IV (eight boys and four girls). Data collection techniques used were observation and tests. The research instruments were the syllabus, lesson plans, student worksheets, and tests. The data analysis techniques were class averages, classical learning completeness, student and teacher activity data analysis. The results obtained an increase in students' speaking skills and curiosity character, as well as the minimum completeness criteria. The result of the average score in the first cycle for speaking skills was 67.91 while the curiosity character was72 and in the second cycle, the speaking skills was 72.25% while the curiosity character was 86%. It means that the Talking Stick learning model improved students' speaking skills and curiosity character.